The atomic scale structure of glass-like carbon obtained from fullerene extract via spark plasma sintering. (December 2016) - Hawelek, L.; Wlodarczyk, P.; Hudecki, A.; Lis, M.; Zackiewicz, P.; Jurkiewicz, K.; Szade, J.; Kubacki, J.; Balin, K.; Fischer, H.E.; Kolano-Burian, A.; Burian, A.
Abstract: The spark plasma sintering technique was successfully used to transform fullerene extract into glass-like carbon. The sintered sample was characterized via thermogravimetry, scanning electron microscopy, X-ray photoelectron spectroscopy, the X-ray and neutron diffraction. To reconstruct the atomic scale structure the diffraction results were combined with computer simulations. The comparative analysis was performed in the form of the structure factor and the pair correlation function in the reciprocal and direct space. In the first approach the two different concepts of graphite-based models have been verified. For such constructed models the pair correlation functions maxima positions indicate the strong differences in comparison with the experimental data. In the second approach the proposed models were constructed successively on the icosahedral from C960 up to C3840 fullerenes fragments. The final model consists of triple layer fullerene C3840 -like fragments in which the isolated pentagon presence guaranties the stronger curvature. The calculated pair correlation function fits the experimental data well and therefore proves that the atomic structure of sintered glass-like materials originated from C60 /C70 fullerene extract consists of defected fullerene C3840 -like fragments. The curvature was assured by isolated pentagon, but the disorder of surrounded hexagonal lattice was modeled and properly reconstructed by the Stone-Thrower-Wales topological defects.